Toxicity of the swainsonine-containing plant Ipomoea carnea subsp. fistulosa for goats and sheep. (15th July 2021) - Oliveira, Carlos Alberto; Riet-Correa, Gabriela; Lima, Everton; Medeiros, Rosane M.T.; Miraballes, Cecilia; Pfister, James A.; Gardner, Dale; Cook, Daniel; Riet-Correa, Franklin
Abstract: In order to determine the toxicity of swainsonine present in Ipomoea carnea for goats and sheep, 12 goats and 12 sheep were divided into 3 groups of 4 goats (G1, G2 and G3) and 3 groups of 4 sheep (S4, S5 and S6) each. Groups G1 and S4 were used as controls; G2 and S5 received 1 mg/kg body weight of swainsonine from plant material and G3 and S6 received 3 mg/kg. Groups G2 and G3 presented the first clinical signs, on average, after the 54th and 39th days of ingestion of the plant, respectively. Groups S5 and S6 presented the first clinical signs, on average, on the 64th and 42nd days of the experiment, respectively. In sheep, in addition to having a longer period of ingestion until the onset of clinical signs, these signs were less severe, being evident only after the animals were forced to move. These results demonstrated that goats are more susceptible to swainsonine poisoning than sheep. Complete regression of clinical signs was observed in 5 goats and 6 sheep. However, three goats and one sheep remained with clinical signs until 120 days of the experiment, suggesting that to control the poisoning the animals should be removed from the pastures immediately after the first clinical signs. There were no significant differences in weight between the different groups, suggesting that for goats ingesting the plant, toxic Ipomoea species can be used as forage for intermittent periods of 15–30 days. Highlights: Poisoning by the swainsonine containing plant Ipomoea carnea occurs more frequently in goats than in sheep. Experimentally, goats are more susceptible to swainsonine than sheep and signs are more severe. Under field conditions, differential poisoning between species is not due to differences in experimental susceptibility. Sheep are more reluctant to consume Ipomoea carnea while grazing compared to goats even when forage availability is low.